Hubungan Capital Intensity Ratio, Firm Size, Digital Transformation terhadap Tax Avoidance dengan CSR sebagai Moderasi - Karlinah, Lady; Tallane, Yoan Yohana; Putri, Vallerie Redyna (Politeknik Ganesha Medan, 2024)
This research analyzes how Firm Size, Digital Transformation, and Capital Intensity Ratio influence Tax Avoidance, with Corporate Social Responsibility as a moderator.